In Defense of Their See: The Bishops of Zagreb (1272-1301) - Nekić, Antun (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
The last quarter of the thirteenth century saw the weakening and ultimately the dying out of the Arpad dynasty, while the figures usually defined as oligarchs were on the rise. The considerable power and influence the Arpads had over the Church was also threatened. The present study takes the case study of the bishopric of Zagreb in the period between 1272 and 1301 in order to see how the bishops of Zagreb operated in this unstable political context, what threats to church’s rights and possessions they encountered and how they responded to them. The paper is organized chronologically and looks at the ways in which the four bishops of Zagreb interacted with the royal court, local oligarchs, prelates of the kingdom, the cathedral chapter, and the middling/lower nobility.